MTXbrooch: fine metal and textile arts for modern contemporary brooch / Nur Syafinaz Mohd Anuar ... [et al.] - Mohd Anuar, Nur Syafinaz; Iskandah, Muhammad Faiz; Daud, Mohd Zamani; Lias, Hamdan (Universiti Teknologi MARA, Kedah, 2019)
Malaysia is one of the countries well known for producing metal-based and textile craft products other than Indonesia and Thailand. However, it was found that metal-based and textile products are being commercialized on their own without incorporating new crafts with the attempts to seriously optimizing the combination of both. This project is an initiative of idea that combines fine metal and textile especially batik in creating modern contemporary brooch that is highly potential to be commercialized. Therefore, this project is conducted to identify the uniqueness and precious impact upon combining both metal and batik to give brand new perspective in jewellery products in Malaysia. The brooch is designed according to subject matters Bangau Perahu (Malay ship figurehead), Wau Bulan (intricately designed Malaysian moon-kite), and Pintu Gerbang Istana Zahar, Kelantan (palace gateway of Istana Zahar, Kelantan) which represent three different themes which are ocean, air, and land. Batik design, on the other hand uses Sulur Bayung from Malay wood carving motif that symbolizes the feelings and Malays way of thinking. Generally, the subject matter and batik motifs are blended to create a Malaysian-identity brooch. The idea of merging both matters will elevate the concept aimed as well as the brooch aesthetical value. The ergonomic aspect is also put into serious attention as it defines the comfort and safety of the wearers. The novelty aspects of this project are the brooch creation and the rare combination of metal and batik. This brooch is highly potential to be commercialized due to its contemporary, attractive and versatile designs which integrates diverse motif and subject matter yet still has outstanding Malaysia identity.